2020
DOI: 10.1371/journal.pone.0232426
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of extrapulmonary tuberculosis among people living with Human Immunodeficiency Virus in Addis Ababa, Ethiopia: A retrospective cohort study

Abstract: Background Extrapulmonary tuberculosis is an emerging public health problem among HIV positives compared to the general population. This study aimed to assess the incidence and predictors of extrapulmonary tuberculosis among people living with HIV in selected health facilities in Addis Ababa, Ethiopia, from 01 January 2013 up to 31 December 2018. Methods A retrospective cohort study design was employed based on data collected from 566 HIV positive individuals. Data were entered using EpiInfo version 7.1 and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
2
11
2
Order By: Relevance
“…Genitourinary TB (GUTB) was diagnosed among 5.6% (27) patients during the study period. Of these, the majority, 81.5%, (22) were male GUTB ((testes (10), scrotal (7), epididymis (5)) and the remaining, 18.5%, (5) were female GUTB ((cervix (2), endometrial (2) and…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Genitourinary TB (GUTB) was diagnosed among 5.6% (27) patients during the study period. Of these, the majority, 81.5%, (22) were male GUTB ((testes (10), scrotal (7), epididymis (5)) and the remaining, 18.5%, (5) were female GUTB ((cervix (2), endometrial (2) and…”
Section: Plos Onementioning
confidence: 99%
“…The national TB programs, however, have focused on PTB because of transmissibility, and likewise, the majority of studies done in Ethiopia focused on PTB [9]. Some of the previously conducted studies in Ethiopia focused on the genotypic characterization of mycobacterium causing EPTB [8,[10][11][12] and other assessed diagnostic modalities accuracy and sensitivity for lymph nodes TB [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. A detailed characterization incorporating sociodemographic, clinical, laboratory, and radiological features of adult EPTB cases is lacking in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of EPTB reports were recorded in the first years of follow-up with lower baseline helper T-lymphocytic cells (CD4 + ; CD = Cluster of differentiation ) counts and anemia found to be independent risk factors for EPTB. Those patients who were taking antiretroviral therapy as well as isoniazid (INH) were shown to have reduced risk of EPTB [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies considered ≥ 45 years of age, female gender, HIV-positive, and the end-stage rental disease as risk factors for EPTB 26 28 . However, our study showed that female gender and ≤ 20 years of age were more likely to have concurrent EPTB, which were consistent with reports from high-burden countries such as Nepal, China and Pakistan 29 31 .…”
Section: Discussionmentioning
confidence: 99%